Maturities and Dynamic Volatility of Sukuk Comparative Study Between a Sukuk and a Conventional Bond Index - Roukiane, Brahim; Marzouki, Abdenbi EL (Asian Development Policy Review, 2018)
Throughout this article, we have tried to compare the dynamics of the volatility of the Sukuk index of different maturities, as well as their conventional counterparts, by carrying out several tests, namely the Student test, the Granger causality test, the Jarque Berra test and the Ljung-Box test, so we modeled the behavior of volatility using the unconditional volatility measured by the monthly standard deviation and the conditional volatility estimated by the GARCH models and EGARCH. Our sample consists of ten index selected from the Dow Jones index of different maturities, the study period ranges from 01/01/2014 to 25/04/2017. We concluded that Sukuk are generally less risky than conventional bonds. Indeed, the modeling of the volatility of the return index by the GARCH and EGARCH models shows that the Sukuk index are significantly and largely less volatile than their conventional counterparts for all maturities. As well as the persistence of the volatility of the Sukuk index is more persistent compared to their conventional counterparts, when the maturity exceeds strictly 5 years and vice versa if the maturity is less than 5 years.